Evaluation of the impact of common methods of implementing building facades in residential buildings in Tehran on energy consumption - Amin Alah Ahadi (مسکن و محیط روستا, 2023)
In this research, conducted with a focus on the eastern, western, and southern regions of Tehran, the cooling and heating loads in buildings facing different geographical directions are compared and the suitable construction materials and methods, cladding materials, and construction details for external separating walls in each geographical direction are identified. For this purpose, simulation tools using Energy Plus software with the graphical interface Design Builder have been used for thermal analysis and energy consumption of the building. The results of this research show that southern units have the lowest total cooling and heating loads, followed by eastern units (16% higher than southern units), western units (17% higher than southern units), and northern units (20% higher than southern units) respectively. The simulation results for different facades generally show that the heating load in the northern units is 30 to 40% higher than the southern units in facades with different construction materials. In western units, this percentage is 20 to 25 percent higher than the southern unit, while in eastern units it is 19 to 22 percent higher. In north-facing units, depending on the type of facade, the cooling load is 0.5 to 0.7 percent higher in facades with different materials compared to the southern unit. In western units, this percentage is 5.6 to 7 percent higher, and in eastern units, it is 5.10 to 11 percent higher. In addition, the impact of using different common materials in Tehran's urban facades, such as composite metal facades, ceramic facades with dry fixing method, ceramic facades with adhesive fixing method, cement facades, concrete panel facades with dry fixing method, dry brick facades, brick facades with adhesive fixing method, dry stone facades (granite, marble, quartzite, and sandstone), and stone facades with adhesive fixing method, on building energy consumption has been investigated. The research results indicate that among common materials, brick is the best facade material, followed by concrete panels, and the best execution method is the dry installation of these materials